AESTHETICS IN MUSIC. A LOOK FROM MARTÍ´S SENSIBILITY FOR THIS ART - García Vázquez, Bárbara M. (Atenas, 2013)
The paper establishes some considerations on the aesthetic component in music out of the concept of aesthetics, and having into account music composers from universal and Cuban culture mentioned by José Martí in many of his works; in some of which he makes a brief characterization of the authors and the works, showing his knowledge about arts and his artistic sensibility. The paper covers part of the life and works of the German composer Giacomo.